What are the data privacy concerns associated with a smart home environment? A Literature Survey - Dai, Min (2018)
In recent years, the smart home market has witnessed substantial growth in the number and variety of products. Although a smart home environment formed by these products can improve the life of the residents, its unique properties (such as monitoring, control, optimisation, and autonomy) have driven the residents to concern about their data privacy. Therefore, this document aims to reveal the data privacy concerns associated with a smart home environment and the causes of these concerns. Through rigorous meta-analysis, numerous concerns regarding (1) the over-collection of personal data, (2) the internal and external unauthorised secondary use of personal data, (3) the improper access to personal data by adversaries, (4) the errors in databases, (5) the excessive automation in decision-making process, (6) the combination of personal data into rich and large dataset, (7) the smart home residents’ control over their personal data, and (8) individuals’ awareness of data privacy practices have been discovered. These concerns are generally caused or exacerbated by (A) the limitations of “one fits all” data policy or poorly localised data policy in meeting individuals’ privacy demands, (B) the inherent nature of the technologies adopted in a smart home environment, (C) the limitations of the privacy protection mechanisms and smart home technologies in preserving the residents’ data privacy, and (D) the consumers’/regulators’ unrealistic data privacy expectations.